Pembatalan Sertipikat Hak Milik Atas Tanah - Noviasih Muharam (Law Faculty of Universitas Bandar Lampung, 2015)
Land is a national treasure determining welfare, justice, sustainability, and harmony for nation and state of Indonesia. Land has multidimensional characteristics such as physical, chemical, biological, social, economic, and magic-religious characteristics and each of them has potential to human welfare. The problems in this research were: how did the conduct of land ownership certificate nullification based on the court decision with permanent legal strength in Land. This research used normative approaches. Data sources were from secondary data. Data were processed with data editing, classification, and systematization with qualitative jurisdiction analysis. The results were obtained the conduct of land ownership certificate nullification based on the court decision with permanent legal strength in Land had been in accordance with prevailing legislation.The researcher suggests that BPN should be more encouraged and immediate in responding the process of land ownership certificate nullification based on the court decision with permanent legal strength.